Evaluasi dan Usulan Pengembangan Energi Terbarukan untuk Keberlangsungan Energi Nasional - Dino Caesaron; Yona Maimury (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Indonesian people currently consume non-renewable energy as their primary energy. It makes Indonesia running out of inventory energy raw materials especially non-renewable energy. Therefore, energy management and conservation are very needed. This study was aimed to define and analyze what become a constraint on renewable energy development, how to socialize renewable energy program to the community and another management program to solve the problems. Fishbone diagram was used to identify the cause problems from the main effect and 5W1H methodology was used to define the proposed improvement.Keywords: Non-renewable energy, renewable energy, energy conservation, fishbone diagram, 5W1H.